2015
DOI: 10.19182/remvt.20557
|View full text |Cite
|
Sign up to set email alerts
|

Analyse de l’évolution du système pastoral du Maroc oriental

Abstract: Le système pastoral des hauts plateaux du Maroc oriental est caractérisé par l’étendue des parcours (3,2 millions d’hectares) et la dominance de l’élevage ovin (1,2 million de têtes). Ce travail, mené à Béni Mathar au nord et à Maâtarka au sud, traite la question des changements d’occupation des terres de parcours et de conduite des troupeaux, à partir de l’hypothèse d’une dégradation des parcours suivie d’une baisse de la pression de pâturage. Cette dynamique est perçue par l’étude de l’occupation des sols en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 2 publications
5
19
0
Order By: Relevance
“…These have shown that over the last few decades there has been a significant intensification of crossing practices between Ouled-Djellal and this breed in private farms: Bechchari et al . 25 described an “invasion phenomenon” characterized by a growing number of Ouled-Djellal in Beni-Guil herds. According to interviews conducted by Bechchari et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have shown that over the last few decades there has been a significant intensification of crossing practices between Ouled-Djellal and this breed in private farms: Bechchari et al . 25 described an “invasion phenomenon” characterized by a growing number of Ouled-Djellal in Beni-Guil herds. According to interviews conducted by Bechchari et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to interviews conducted by Bechchari et al . 25 , it seems that the expansion of the Ouled-Djellal breed is mainly the result of the sedentarization and intensification of agriculture, i . e ., breeders, who are under increasing pressure to improve productivity, favor Ouled-Djellal for its market value.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained by the breeding system and the pasture availability and diversity between studied cradles. In the Cr2, the breeding system is more extensive than Cr1, where the Artemisia herbaalba and Stipa tenacissima formations are in an advanced degradation state compared to Cr2 [8]. Consequently, the farmers of Cr1 adopt a semiextensive system using barley and Lucerne hay as a food supplementation to satisfy the different needs of their herds.…”
Section: Resultsmentioning
confidence: 99%
“…These include a fall in forage production from rangelands and amplified water stress, leading to a scarcity of fodder and water resources (Mahyou et al, 2010;Maâtougui et al, 2011), which in turn increases competition over existing pastoral resources (Bourbouze and El Aich, 2000). In addition, climate change and extremes (droughts) are one of the main factors responsible for rangeland degradation in the high plateaus of eastern Morocco, which has also been generated by overgrazing, clearing and conversion of rangelands into cultivated land as well as an inefficient pasture management (Mahyou et al, 2010;Maâtougui et al, 2011;Schilling et al, 2012;Bechchari et al, 2014;Lang et al, 2021). Furthermore, extreme weather events induced by CC have increased poverty among poor smallscale pastoralists and rural-urban migration (El Harizi et al, 2005) and exacerbated social inequalities among pastoralists, especially during persistent droughts (Schilling et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…After severe or prolonged droughts, it is very difficult for small-scale pastoralists to reconstitute their herds. Conversely, large-scale pastoralists are relatively less dependent on natural resources for the formation of their income, have the financial means to buy animal feed even in times of crisis, and above all they can reconstitute their herds once the climatic conditions become more favorable or after the advent of subsidized feed (Kuhn et al, 2010;Bechchari et al, 2014). Hence, the poorest pastoralists with livestock -based livelihoods J o u r n a l P r e -p r o o f are hardest hit owing to their increased vulnerability to the adverse consequences of climate change and extremes (Snaibi, 2020b).…”
Section: Introductionmentioning
confidence: 99%